PENGUATAN NILAI-NILAI KARAKTER NASIONALIS DENGAN PEMBELAJARAN ADAPTIF (Studi Kasus di SMK Purnama Kabupaten Magelang) - Supriyono, Tjatur Supriyono; Endang Sri Kurniatun; Agustina Dwi MP (JURNAL DWIJA KUSUMA, 2024)
The sense of nationalism is diminishing due to globalization and current technological advances. One of them lost its sense of nationalism and knew more of Western artists than of heroes. Pancasila education is a very important education to instill the attitude and morality of the participants through the development and strengthening of the character of love for God and love for the homeland. Therefore, SMK Purnama Tempuran designed a program to strengthen the nationalist character of students through learning. The objective of this study is to explain how the application of nationalist character values in the learning process in schools and the factors that support and hinder the implementation of these values into adaptive learning approaches. This research uses a descriptive qualitative approach, which is a kind of field study research. The results of the research show that the cultivation of nationalist character values in adaptive learning is carried out in two stages: planning and implementation. Factors supporting the cultivation of nationalist character values include support from the head, means and facilities, and teacher-student collaboration.